PENGEMBANGAN PERANGKAT PEMBELAJARAN MODEL PROBLEM BASED LEARNING DENGAN PENDEKATAN SAINTIFIK PADA MATERI PROKLAMASI KEMERDEKAAN INDONESIA UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA KELAS XI SMKN 12 SURABAYA - Mintarsih, Fatayat Ridlo (The Indonesian Journal of Social Studies, 2017)
This study aims to produce the quality and effective learning device using Problem Based Learning model with scientific approach.The study was conducted in three phases following the design of the 4-D mode of thiagarajan (1974). The three stages are the preliminary stage (define), the planning (design), and stage of development (develop). This type of research is the R & D to design the control group pre-test - post-test design, the subject of this research is class 11 DKV-2 with the number of students 30 as an experimental class and class 11 DKV-1 with the number students 24 as grade control. Collection of research data obtained through observation, tests and questionnaires. The results were obtained the following data, first quality learning outcomes device that includes the results of the validation RPP reached an average 3.39 (both categories), the validation results of student worksheet reach an average of 3.56 (both categories) the results of the validation handout reaches an average of 3.70 (both categories) the implementation of learning reaches an average of 3.3 (both categories), the third student learning outcomes classified as either category, In the spiritual attitude and social competence quite good, the competence of knowledge suggests that a validation item about reaching 3.78 (both categories) than the level of mastery learning in the experimental class reached 83.3%, while the level of completeness of the control class reached 73.6%. On commpetency skills on classified quite good categories. Fourth, the response showed students showed that students enjoy participating in the learning process with a model Problem Based Learning with a scientific approach.